Knowledge, attitude, and practices regarding COVID-19 among obstetric health care professionals in a tertiary care hospital, Karachi, Pakistan - Shahwar, Dur-e; Naz, Sumaira; Saleem, Shamila; Malik, Ayesha; Raza, Amia (International Journal Of Community Medicine And Public Health, 2021)
Background: The recently ongoing pandemic COVID-19 tramp in number of healthcare professionals (HCPs). They are facing the challenge of managing pregnant patients and their unborn babies. This study was done to evaluate the knowledge, attitude, and practices (KAP) among obstetric health care workers towards the COVlD-19. Methods: This cross-sectional study was conducted among OHCP at Aga Khan University Hospital, Karachi, Pakistan. For each correct answer 2 points were assigned. Scores for each category were calculated. According to Bloom’s cut-off good knowledge was considered for >80% scores, for practice and attitude scores of 8 and 6 were considered as appropriate respectively. Results: A total of 124 responses were analyzed. Most of the responders were females (97.6%) in the age group of 25-50 years (96%). Most obstetrics healthcare professionals had good knowledge and practice scores (n=92.75%, 91.1%, respectively). We also observed positive attitude scores (n=92.7%) with a mean COVlD-19 knowledge score was 18.71±3.34 (range: 10-24) whereas the mean score of practice was 5.76±0.68 (range: 0-6) suggesting good knowledge and practice. The mean attitude score was 8.60±1.37 (range: 2-10) indicating a positive attitude. However, in univariate analysis, we did not find a significant association with categorical variables. Conclusions: There was comparatively good knowledge regarding Covid-19 among obstetric healthcare workers. Implementation and dissemination of hospital infection control guidelines and training against COVID-19 infection helped to attain appropriate knowledge translating into positive attitude and practices among healthcare workers.